The effect of liver metastasis on efficacy of immunotherapy plus chemotherapy in advanced lung cancer. (March 2020) - Qin, Bao-Dong; Jiao, Xiao-Dong; Liu, Jun; Liu, Ke; He, Xi; Wu, Ying; Ling, Yan; Duan, Xiao-Peng; Qin, Wen-Xing; Wang, Zhan; Zang, Yuan-Sheng
Abstract: The present study aimed to evaluate the effect of liver metastases on the efficacy from the combination of PD-1/PD-L1 inhibitor with chemotherapy as first-line treatment in lung cancer using the meta-analysis. A total of 8 randomized controlled trials (RCTs) were included. In patients without liver metastases, PD-1/PD-L1 inhibitor plus chemotherapy could decrease the risk of progression by 40% and risk of death by 29% (HR = 0.60; 95%CI, 0.55– 0.65 and HR = 0.71;95%CI, 0.58–0.90 respectively). In patients with liver metastases, PD-1/PD-L1 inhibitor plus chemotherapy could decrease the risk of progression by 31% and risk of death by 21% (HR = 0.69;95%CI, 0.58–0.81; and HR = 0.79; 95%CI, 0.62–0.80, respectively). The pooled ratios of PFS-HRs and OS- HRs reported in lung cancer patients with liver metastases versus those without liver metastases were 1.11 (95%CI, 0.92–1.34) and 1.03 (95%CI, 0.80–1.35), respectively, suggesting that lung cancer patients with and without liver metastases could obtain comparable efficacy.